2005
DOI: 10.1038/sj.bmt.1704963
|View full text |Cite
|
Sign up to set email alerts
|

Poor nutritional status prior to peripheral blood stem cell transplantation is associated with increased length of hospital stay

Abstract: Summary:The nutritional status of patients prior to peripheral blood stem cell transplantation (PBSCT) and its impact on length of hospital stay is not well described in the literature. The nutritional status of 66 consecutive patients (46 m:20 f); and the mean age 58.7712.0 years was determined a maximum of 2 weeks pre-transplantation using the scored Patient-Generated-Subjective Global Assessment (PG-SGA). According to the global assessment, 73% patients were well nourished, 23% moderately malnourished and 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(57 citation statements)
references
References 14 publications
3
52
0
2
Order By: Relevance
“…The patient-generated SGA (PG-SGA) is a further modification of the SGA and has been specifically developed for patients with cancer (Ottery, 1996). The PG-SGA has been used for nutritional assessment in patients with various types of cancer such as cancer of the oesophagus, stomach, pancreas, lung, colorectum, breast and head and neck (Bauer et al, 2002;Persson et al, 2002;Isenring et al, 2003;Ravasco et al, 2003Ravasco et al, , 2005Bauer and Capra, 2005;Desbrow et al, 2005;Horsley et al, 2005;Segura et al, 2005). Bauer et al (2002) compared the scored PG-SGA with the SGA for patients with cancer and suggested the PG-SGA be used for further studies to detect malnutrition in cancer populations.…”
Section: Introductionmentioning
confidence: 99%
“…The patient-generated SGA (PG-SGA) is a further modification of the SGA and has been specifically developed for patients with cancer (Ottery, 1996). The PG-SGA has been used for nutritional assessment in patients with various types of cancer such as cancer of the oesophagus, stomach, pancreas, lung, colorectum, breast and head and neck (Bauer et al, 2002;Persson et al, 2002;Isenring et al, 2003;Ravasco et al, 2003Ravasco et al, , 2005Bauer and Capra, 2005;Desbrow et al, 2005;Horsley et al, 2005;Segura et al, 2005). Bauer et al (2002) compared the scored PG-SGA with the SGA for patients with cancer and suggested the PG-SGA be used for further studies to detect malnutrition in cancer populations.…”
Section: Introductionmentioning
confidence: 99%
“…Rationale: HCT patients are predisposed to developing malnutrition because of their underlying disease, the conditioning regimen, and other treatment-related toxicities. 139,[143][144][145] Increase in morbidity 139,143,145 and mortality 145 has been reported in malnourished patients receiving HCT. Alterations in nutrition status persist long after transplantation, with as many of 50% of patients not returning to pre-transplant weight at 1 year.…”
Section: B Nutrition Support Therapy In Hematopoietic Cell Transplanmentioning
confidence: 99%
“…3 It has previously been shown that poor nutritional status before SCT may prolong hospital stay. 4 In critically ill patients, parenteral nutrition (PN) has been associated with mucosal atrophy and an increased risk of infectious complications. 5 PN may also change the local cytokine production profile, resulting in low levels of interleukin (IL)-4 and IL-10.…”
Section: Introductionmentioning
confidence: 99%